Keuntungan dan Kerugian Diet Vegetarian pada Remaja : Kajian Literatur - Rebecca Sharlene Ayentha Herdianto; Adji Aisy Tavania Zahra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Adolescence is a critical period characterized by increased nutritional requirements. Vegetarian diets are increasingly adopted by adolescents for health, ethical, and environmental reasons. However, this dietary pattern presents both potential benefits and risks that require comprehensive evaluation. This study employed a narrative review method by conducting a literature search through the PubMed and Google Scholar databases. Article selection was carried out using the PRISMA flow diagram based on predetermined inclusion and exclusion criteria. The quality of the included studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. Eligible articles were then synthesized narratively according to major themes. The findings indicated that vegetarian diets among adolescents were associated with lower body mass index (BMI), improved lipid profiles, higher diet quality, and greater intakes of fiber, folate, vitamin C, and magnesium. Furthermore, vegetarian diets may promote nutritional awareness and healthier eating behaviors. However, poorly planned vegetarian diets may increase the risk of deficiencies in vitamin B12, iron, calcium, zinc, vitamin D, and omega-3 fatty acids, as well as potentially increase the risk of anemia and restrictive eating behaviors. Vegetarian diets can provide significant health benefits for adolescents when appropriately planned. Nutrition education, regular nutritional status monitoring, the consumption of fortified foods, and appropriate supplementation are essential to ensure adequate nutrient intake and support optimal adolescent growth and development.